La discrétion du volcan Katla - Elisabeth Bernard (Ateliers d'Anthropologie)
Vík í Mýrdal, a small village in southern Iceland, is home to an eminently cosmopolitan population that lives on the region’s tourist activity. Looming over the village, the subglacial volcano Katla has worried Iceland’s surveillance institutions for years, as they attempt to ready themselves for the next eruption, whose potential for destruction was forecast long ago. Locally, the volcano arouses worry, passion, even indifference. Having different degrees of habituation to the immediate proximity of a volcano, the Icelanders and foreigners who live in the village must learn to familiarise themselves with this living entity—whose discretion is proportional to its dangerousness—as soon as a non-eruptive event disturbs the social space. This article considers how villagers develop a personal relationship thanks to the in situ development of skills enabling them to forge a mode of attention to, and specific geosocial relations with, this volcano.